(untitled) (Emancipação, 2022)
This article aims to evaluate the implementation process of the Early Childhood Program in SUAS, in the city of Recife/PE, focusing on the implementation and training processes. The methodology was bibliographic and empirical research. In data collection, 35 executing agents of the Program were interviewed remotely through semi-structured interviews. Conclusions: although municipal management has made efforts to incorporate the PCF into the Social Assistance Policy, offering counterpart, qualifying the technical team, planning its activities and necessary flows with the social assistance network, as a response to the cause of Early Childhood, it was inevitable to follow the regulations s of the Program; the effort of municipal management proved powerless to minimize the obstacles contained in its formulation and nature as a public response to the problem of Early Childhood with the usufruct families. The Program is limited in its potential response to the problem, as its reason for being.